DIKSI DALAM WACANA IKLAN BERBAHASA INDONESIA Satu Kajian Sosiopragmatik - Tri Sulistyaningtyas (Jurnal Sosioteknologi, 2008)
The language used in the advertisements of both printed and electronic mass media is often unsuitable with the grammatical rules of Bahasa Indonesia. Due to the ineffective use of Bahasa Indonesia, the intended message conveyed is not accomplished. The facts show that the advertisements are expressed in simple, contextual, and familiar language to the targeted audience. This condition concerns many people. One of the reasons for the advertisements expressed in such a way is because applying the SPOK rule and effective sentences will result in long and unattractive wording. In every advertisement, a catcher "“ such as sound, picture, and verbal language "” has to be used so that the potential consumers will be directly connected to the product being advertised by listening to, looking at, and reading the catcher. The study shows that those catchers are categorized as locution, illocution, and perlocution. Further, it was found that they belong to the direct and indirect illocution having an assertive function. The wording in the advertisement should represent the intended meaning because some words could be interpreted differently by a certain cultural group of people. Therefore, the choice of words should go well with their language norm. Key words: Advertisement, Language rules, catcher, people's language norm